Keputusan pembelian produk vitamin c di masa pandemi covid - 19 - Kurnia Kusumawati; Sahat Saragi; Lies Putrianti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Vitamin C products during the COVID-19 pandemic had a significant sales increase. Buying decisions not only influenced by products such as price and quality, but also influenced by factors that exist around consumers, for example culture, socio-economic, psychological personality. This study aims to determine the factors that influence buying decisions for vitamin C products during the COVID-19 pandemic. The survey was taken by non-probability sampling with purposive sampling technique on male or female respondents who bought vitamin C products at pharmacies in Bogor district. Based on the results of SEM statistical analysis using Lisrel, it is known that price variables, quality variables, cultural variables, socio-economic variables and personal-psychological variables have a positive and significant effect on buying decision variables. During the COVID-19 pandemic, the most influential factors on buying decisions for vitamin C products were personal-psychological factors followed by socio-economic factors, cultural factors, quality factors and price factors.